Struktura funkcjonalna a poziom rozwoju społeczno-gospodarczego gmin wiejskich powiatu opolskiego w 2003 roku - Rajchel, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this paper is to show the functional structure and the social situation of the rural communes in the Opole county. All the investments and local governments dealings seems to show the advance of the spatial planning processes. In this study the demographic type of the communes was established with the use of the statistic data concerns population, like: age, sex, migration, growth rate. Other data concerns business enterprises was also used. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 400-413